At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

-3(2t-1)=t+t+t+3 pls help

Sagot :

31507

Answer:

t=0

Step-by-step explanation:

First, we expand everything. The left-hand side is -3(2t) - 1(-3), and we expand it to be -6t+3. The right-hand side is t+t+t+3, and we can reduce it to 3t+3. Now that we have both sides of the equation, we set them to each other.

-6t+3=3t+3 (subtract 3 on both sides)
-6t=3t (add 6t to both sides)
9t =0 (divide by 9)
t=0